Anal Phase Analysis of Thomas Hardy’s “Tess of The D’urbervilles” - Safnidar Siahaan (English Department, University of Riau Kepulauan, Batam,Indonesia, 2017)
The research offers about the development phase analysis in Hardy’s novel “Tess of the D’Urbervilles”. This novel describes Tess as the victim of men who fall in love with her. Tess is one of Hardy's most sympathetic protagonists. She is as likeable as a literary character found in all of English literature. Throughout the novel, Hardy develops Tess as a character and describes her simple beauty. She is attractive to all men, and even her attempts to change her appearance are not enough to hide her natural beauty. Further in the story of the novel, Tess is depicted as a person of near divine qualities when she baptizes Sorrow before he dies. Hardy calls the effect on her siblings as a transfiguring effect